2016
DOI: 10.2174/1874210601610010117
|View full text |Cite
|
Sign up to set email alerts
|

Odontogenic Keratocyst in Children: A Review

Abstract: Objective:Is to highlight the characteristics and management of odontogenic keratocyst in children onlyMaterial and Method:Computerized search in pubmed between (2005-2015) using specific words such as odontogenic keratocyst in children, odontogenic keratocyst association with Gorlin-Goltz syndrome with abstract written in English only.Result:During computerized literature search 77 articles in the years (2005-2015) were found. All these publications were miscellaneous studies including case series and case re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
11

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 26 publications
0
9
0
11
Order By: Relevance
“…Keratocysts in syndromic patients can present, on average, five per patient, in addition to a higher recurrence rate after enucleation compared to non-syndromic patients. Because of this, it is recommended follow-up for a long period (annually for five years and biannually, for the entire life of the patient) [7,11,20]. Khaliq, et al [11] when evaluating seven syndromic patients, found that all had multiple keratocysts as the first manifestation of the syndrome, most of which were located in the mandible (77%), in an unilocular pattern (71%), associated with teeth (88%).…”
Section: Discussionmentioning
confidence: 99%
“…Keratocysts in syndromic patients can present, on average, five per patient, in addition to a higher recurrence rate after enucleation compared to non-syndromic patients. Because of this, it is recommended follow-up for a long period (annually for five years and biannually, for the entire life of the patient) [7,11,20]. Khaliq, et al [11] when evaluating seven syndromic patients, found that all had multiple keratocysts as the first manifestation of the syndrome, most of which were located in the mandible (77%), in an unilocular pattern (71%), associated with teeth (88%).…”
Section: Discussionmentioning
confidence: 99%
“…Removal of the whole cyst completely, with extraction of the teeth or tooth buds involved by the lesion, is a radical surgical treatment that gives the smallest percentage of relapses. However, if it is possible to preserve the teeth, considering the functional, aesthetic, and psychological aspects, the methods of conservative surgical treatment should be used as the method of choice [3,12,13]. The two-stage method of enucleating a cyst has been successfully used in the Department of Oral Surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of cases cured was 88.1% and 82.2%, respectively, with a 5-year observation period [14]. In patients treated at developmental age, follow-up examinations are recommended every 6 months [13]. In the case of the above-mentioned patient, the recurrence occurred approximately after 7 years from the moment of diagnosing and starting the two-stage treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The parakeratin surface typically appears corrugated, the basal layer is well defined and frequently palisaded with hyperchromatic nuclei and focal areas showing reversed nuclear polarity. [3,7,8,41]. OKC's do not cause metastases or lymph node invasion and do not form tumoral masses.…”
Section: Introductionmentioning
confidence: 99%
“…This is an autosomal dominant multisystem disease that leads to multiple OKC's, as well as several nevoid basal cell carcinomas, palmar or plantar pits, calcification of falx cerebri, and skeletal abnormalities. The Gorlin Goltz syndrome is associated with mutations in the PTCH gene situated on 9q22.3-q31, with described mutation rates of 80-90% [1,7,8,16,19,20]. The established treatment modalities for OKC's can be divided into radical and conservative treatment options.…”
Section: Introductionmentioning
confidence: 99%